The Static and Dynamic Compressive Behaviour of Selected Aluminium Alloys - R. WINZER; A. GLINICKA (Engineering Transactions, 2014)
The mechanical properties of structural aluminium alloys EN AW-5083 and EN AW-6082 in the ‘H111’ and ‘T6’ conditions, respectively, subjected to compressive loadings in the quasi- static and dynamic strain rate regimes, are investigated. Both alloys are used as structural components not only in car body design or ship building, but also in civil engineering. There- fore, compression tests at room temperature were conducted using a servohydraulic Instron machine, in order to determine the materials‘ behaviour at low and intermediate rates of defor- mation. In addition, to predict the dynamic response of these materials, the Split Hopkinson Pressure Bar (SHPB) technique was utilized. For alloy 5083-H111, a changeover from negative to positive strain rate sensitivity at dynamic strain rates is observable, whilst alloy 6082-T6 exhibits a mild trend towards positive strain-rate sensitivity. Furthermore, the coefficients of the Johnson-Cook model, that are valid under dynamic conditions, are determined. The finite element simulation of SHPB experiments shows that the constitutive model represents the materials’ behaviour quite well.